2016
DOI: 10.16920/jeet/2016/v30i1/97427
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Student Engagement in a Blended Resident and Online Course Using Clickers and Embedded Questions

Abstract: Abstract- Keywords -This paper describes the use of Clickers (small, mobile phone like electronic devices) and embedded questions in streaming videos for the purpose of student engagement in a course that was taught with a blended delivery model in a live resident classroom and also delivered to distance education students online. In order to provide the ability for instructors to engage students in a rich interactive environment, a creative use of Clickers and embedded questions was developed for a course in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, these authors and other recent literature reviews indicated that there were few studies focusing specifically on student engagement in BL (Halverson et al, 2014;Martin et al, 2017;Pima et al, 2018;Raes et al, 2019). Most existing publications also investigated single courses (e.g., Binnewies & Wang, 2019;Cundell & Sheepy, 2018;Raes et al, 2020), specific activities (e.g., Foogooa & Ferdinand-James, 2017;Kulkarni & Iwinski, 2016;Tan & Hew, 2016), or aspects of student engagement (e.g., Berry, 2019;Truhlar et al, 2018). Consequently, given the potential for enhanced student engagement in BL, numerous authors have called for pursuing research on student engagement in BL (Drysdale et al, 2013;Graham, 2019;Halverson et al, 2014;Henrie et al, 2015;Manwaring et al, 2017).…”
Section: Student Engagement In Blended Learningmentioning
confidence: 99%
“…Nevertheless, these authors and other recent literature reviews indicated that there were few studies focusing specifically on student engagement in BL (Halverson et al, 2014;Martin et al, 2017;Pima et al, 2018;Raes et al, 2019). Most existing publications also investigated single courses (e.g., Binnewies & Wang, 2019;Cundell & Sheepy, 2018;Raes et al, 2020), specific activities (e.g., Foogooa & Ferdinand-James, 2017;Kulkarni & Iwinski, 2016;Tan & Hew, 2016), or aspects of student engagement (e.g., Berry, 2019;Truhlar et al, 2018). Consequently, given the potential for enhanced student engagement in BL, numerous authors have called for pursuing research on student engagement in BL (Drysdale et al, 2013;Graham, 2019;Halverson et al, 2014;Henrie et al, 2015;Manwaring et al, 2017).…”
Section: Student Engagement In Blended Learningmentioning
confidence: 99%
“…More generally, few studies have specifically addressed student engagement in blended learning in their research questions and almost none were situated in blended online courses (Halverson et al, 2014; Martin et al, 2017; Pima et al, 2018; Raes et al, 2019). Most studies also investigated single courses (e.g., Binnewies & Wang, 2019; Cundell & Sheepy, 2018; Raes et al, 2020) and/or specific activities within a course (e.g., Foogooa & Ferdinand‐James, 2017; Kulkarni & Iwinski, 2016; Tan & Hew, 2016). Notably, although student engagement is recognized as malleable through instructional strategies (Christenson & Reschly, 2012; Kahu, 2013; Lawson & Lawson, 2013), how these actually influence student engagement in blended learning, and particularly in blended online courses, is still unclear (Graham, 2019; Manwaring et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, few studies have specifically addressed student engagement in blended learning in their research questions and almost none were situated in blended online courses (Halverson et al, 2014;Martin et al, 2017;Pima et al, 2018;Raes et al, 2019). Most studies also investigated single courses (e.g., Binnewies & Wang, 2019;Cundell & Sheepy, 2018;Raes et al, 2020) and/or specific activities within a course (e.g., Foogooa & Ferdinand-James, 2017;Kulkarni & Iwinski, 2016;Tan & Hew, 2016).…”
mentioning
confidence: 99%
“…Video lectures as well as assignments are assigned to the students on a weekly basis. Owing to the highly technical nature of the course, we also increase student engagement by using clicker and embedded questions [8,9]. We also assign what are known as virtual laboratory experiments to further deepen students' understanding of the subject matter.…”
Section: Corresponding Authormentioning
confidence: 99%